PEMBINAAN PRESTASI ATLET PENCAK SILAT PELATIHAN DAERAH (PELATDA) DI KABUPATEN PATO (Indonesian Journal for Physical Education and Sport, 2021)
IPSI Pati is a martial arts association that forms regional training with the aim of fostering regional athletes towards maximum achievement. The purpose of this study was to find out about the development of pencak silat achievement in Pati Regency. Factors that influence sports coaching include other organizations, training programs, recruitment processes for athletes and coaches, facilities and infrastructure, as well as management as the main factors for the implementation of performance coaching in Pati Regenc This research is a descriptive qualitative approach with data using the method of observation, interviews, and documentation. Data analysis techniques using data triangulation techniques, data analysis, data reduction, data presentation an…